A Chemical Blowing Strategy to Fabricate Biomass‐Derived Carbon‐Aerogels with Graphene‐Like Nanosheet Structures for High‐Performance Supercapacitors. Issue 11 (14th May 2019) - Zhang, Hai; Zhang, Ze; Luo, Jin‐Di; Qi, Xing‐Tao; Yu, Ji; Cai, Jian‐Xin; Wei, Jun‐chao; Yang, Zhen‐Yu
Abstract: The efficient exploitation and utilization of low‐cost and biomass‐derived carbon materials will play an active role in developing sustainable energy storage systems. However, the difficult morphology control and incomplete activation limits their pervasive application in electrochemical energy storage. Inspired by the famous Chinese folk handicraft of sugar‐figure blowing, biomass‐derived carbon aerogels (GCA) with 2 D graphene‐like thin nanosheets were fabricated by a simple chemical blowing strategy from a viscous agaric solution obtained through hydrothermal treatment of agaric. A chemical blowing agent (NH4 Cl) was used to effectively exfoliate the bulk biomass‐derived carbon flake into 2 D graphene‐like nanosheets, which resulted in a highly porous structure and high specific area (2200 m 2  g −1 ) after the activation process. As a result, a high specific capacitance of 340 F g −1 at 3 A g −1 and a high specific energy of 25.5 Wh kg −1 at a power density of 2 kW kg −1 was obtained for the GCA electrode, which can be attributed to the abundant electrochemically active surfaces, short ion transport paths, and effective electrolyte infiltration.. This work demonstrates an effective and low‐cost strategy to prepare hierarchical and well‐organized porous biomass carbon materials with graphene‐like nanosheets for high‐performance supercapacitors. Abstract : Get blown away : A facile chemical blowing strategy inspired by sugar‐figure blowing—a Chinese folk handicraft—is used to fabricate a biomass‐derived carbon aerogel with graphene‐like nanosheet structures for high‐performance supercapacitors.